Sphingoid base synthesis is required for oligomerization and cell surface stability of the yeast plasma membrane ATPase, Pma1 - Wang, Qiongqing (The National Academy of Sciences, 2002)
The plasma membrane H(+)-ATPase, Pma1, is an essential and long-lived integral membrane protein. Previous work has demonstrated that the Pma1-D378N mutant is a substrate for endoplasmic reticulum (ER)-associated degradation and causes a dominant negative effect on cell growth by preventing ER export of wild-type Pma1. We now show that Pma1-D378N is ubiquitylated, and it heterooligomerizes with wild-type Pma1, resulting in ubiquitylation and ER-associated degradation of wild-type Pma1. In temperature-sensitive lcb1-100 cells, defective in sphingoid base synthesis, Pma1 fails to oligomerize. At 30°C, lcb1-100 is a suppressor of pma1-D378N because wild-type Pma1 fails to heterooligomerize with Pma1-D378N; wild-type Pma1 moves to the cell surface, indicating that oligomerization is not required for delivery to the plasma membrane. Even in the absence of Pma1-D378N, wild-type Pma1 is ubiquitylated and it undergoes internalization from the cell surface and vacuolar degradation at 30°C in lcb1-100 cells. At 37°C in lcb1-100 cells, a more severe defect occurs in sphingoid base synthesis, and targeting of newly synthesized Pma1 to the plasma membrane is impaired. These data indicate requirements for sphingolipids at three discrete stages: Pma1 oligomerization at the ER, targeting to the plasma membrane, and stability at the cell surface.